2008
DOI: 10.1007/s00894-008-0317-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for lack of inhibition of fish goose-type lysozymes by a bacterial inhibitor of lysozyme

Abstract: It is known that bacteria contain inhibitors of lysozyme activity. The recently discovered Escherichia coli inhibitor of vertebrate lysozyme (Ivy) and its potential interactions with several goose-type (g-type) lysozymes from fish were studied using functional enzyme assays, comparative homology modelling, protein-protein docking, and molecular dynamics simulations. Enzyme assays carried out on salmon g-type lysozyme revealed a lack of inhibition by Ivy. Detailed analysis of the complexes formed between Ivy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Vanderkelen et al found that PliG could inhibit the activity of gLYZ from goose, salmon and larvacean [47]. The different effect of PliG on MGgLYZ1 and MGgLYZ2 might be ascribed to negative electrostatic environment in the entire substrate binding crevice and different electrostatic surface properties in their three-dimensional structure [48].…”
Section: Discussionmentioning
confidence: 99%
“…Vanderkelen et al found that PliG could inhibit the activity of gLYZ from goose, salmon and larvacean [47]. The different effect of PliG on MGgLYZ1 and MGgLYZ2 might be ascribed to negative electrostatic environment in the entire substrate binding crevice and different electrostatic surface properties in their three-dimensional structure [48].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the finding that (i) the production of Ivyc and its homologs is limited to Gram-negative bacteria rather than to Gram-positive bacteria, which possess exposed peptidoglycan and (ii) they are localized to the periplasm rather than to the external milieu was considered a paradox (10). Compounding this paradox is the fact that the Ivyc-like proteins have limited specificity, and they are weak inhibitors of only a subset of the G-type lysozymes (10,17). Furthermore, despite its similarity, Ivyp2, which is produced by some pseudomonads, does not inhibit any type of lysozyme, and its function remained unknown (10).…”
Section: Discussionmentioning
confidence: 99%
“…2 and, perhaps not unexpectedly, the proteins are organized generally according to phylogeny of the producing bacteria. Each member of the Ivyc/p1 family is characterized by the CKPHDC consensus sequence, which has been demonstrated to be essential for binding to C-type lysozymes (10,17). The Ivyp2 paralogs, represented by P. aeruginosa Ivyp2 as the prototype, lack this consensus sequence but possess instead the consensus motif CEXXDXC.…”
Section: Identification and Phylogenetic Analysis Of Ivy Homologs Andmentioning
confidence: 99%
“…Ivy, on the other hand, weakly inhibited g-type lysozyme from goose egg white (GEWL) [19] but not from salmon (SalG). Using homology modeling, protein-protein docking and molecular dynamics simulations, Kyomuhendo et al [20] were able to explain the weak interaction of Ivy with GEWL, and predicted that none of the known fish g-type lysozymes would be inhibited because of their different electrostatic surface properties and curvature. Further, a unique feature of all g-type lysozymes, both from terrestrial and from aquatic organisms, is the involvement of three active residues Glu 73 , Asp 86 en Asp 97 (numbering as in GEWL) [7,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Using homology modeling, protein-protein docking and molecular dynamics simulations, Kyomuhendo et al [20] were able to explain the weak interaction of Ivy with GEWL, and predicted that none of the known fish g-type lysozymes would be inhibited because of their different electrostatic surface properties and curvature. Further, a unique feature of all g-type lysozymes, both from terrestrial and from aquatic organisms, is the involvement of three active residues Glu 73 , Asp 86 en Asp 97 (numbering as in GEWL) [7,[20][21][22]. While Glu 73 has obvious counterparts in c-and i-type lysozyme (respectively Glu 35 and Glu 11 ) [2,21], the latter have only one aspartate residue (respectively Asp 52 and Asp 30 ) contributing to catalysis.…”
Section: Introductionmentioning
confidence: 99%